2001
DOI: 10.1016/s0304-4165(01)00185-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, chemical modifications and in vitro anticoagulant properties of an exopolysaccharide produced by Alteromonas infernus

Abstract: A new low-molecular-weight`heparin-like' component was obtained from an exopolysaccharide produced by a mesophilic strain found in deep-sea hydrothermal vents. Data concerning the structure of the native high-molecular-weight exopolysaccharide (10 6 g/mol, 10% sulfate content) are reported for the first time. Two depolymerization processes were used to obtain low-molecular-weight (24^35U10 3 g/mol) oversulfated fractions (sulfate content 20 or 40). Nuclear magnetic resonance studies indicated that after sulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…This negative charge helps buffering the cells against fluctuating salinity experienced in the marine environments [36] . Sulfated EPSs isolated from bacteria have shown to possess anticoagulant, antioxidant and bone healing properties [8,37] , similarly acetyl and phosphate groups in the EPS also render biologically important properties [38,39] . Ability of the EPS to scavenge free radicals is another property of biological importance.…”
Section: Discussionmentioning
confidence: 99%
“…This negative charge helps buffering the cells against fluctuating salinity experienced in the marine environments [36] . Sulfated EPSs isolated from bacteria have shown to possess anticoagulant, antioxidant and bone healing properties [8,37] , similarly acetyl and phosphate groups in the EPS also render biologically important properties [38,39] . Ability of the EPS to scavenge free radicals is another property of biological importance.…”
Section: Discussionmentioning
confidence: 99%
“…Vincent et al [32] described the isolation of Alteromonas sp. from the epidermis of a polychaete annelid, Alvinella pompejana , living in the deep sea hydrothermal vents of the East Pacific Rise, able to produce a heteropolysaccharide with high levels of uronic acids and pyruvate, and showing anticoagulant and bone healing properties [33,34,35]. Bozzi et al .…”
Section: Marine Eps Producers: Conventional and Non-conventional (mentioning
confidence: 99%
“…The molecular weight of this LMW-EPS was determined as previously described by high-performance size-exclusion chromatography (HPSEC) using pullulan as standard. 7 Pullulan is a neutral glucan, whereas LMW-EPS is highly negatively charged polysaccharide. Consequently, such a calibration, which does not allow an exact measure of molecular mass, was used only for having a rough estimation of MW and homogeneity.…”
Section: Preparation Of Partially Hydrolyzed Exopolysaccharides (Lmw-mentioning
confidence: 99%
“…8 Affinity co-electrophoresis experiments performed in the presence of antithrombin or heparin co-factor II showed that all chains of sulfated LMW-EPS bound antithrombin strongly while only a subpopulation did the same with heparin co-factor II. 7 This latter result strongly suggests that the anticoagulant activity is modulated not only by the sulfate content, but also by the position of sulfate groups along the polysaccharide chain.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation